2021
DOI: 10.1007/s11442-021-1853-9
|View full text |Cite
|
Sign up to set email alerts
|

Geomorphology-oriented digital terrain analysis: Progress and perspectives

Abstract: Digital terrain analysis (DTA) is one of the most important contents in the research of geographical information science (GIS). However, on the basis of the digital elevation model (DEM), many problems exist in the current research of DTA in geomorphological studies. For instance, the current DTA research appears to be focused more on morphology, phenomenon, and modern surface rather than mechanism, process, and underlying terrain. The current DTA research needs to be urgently transformed from the study of lan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(39 citation statements)
references
References 84 publications
0
39
0
Order By: Relevance
“…The spatial resolution of all the factors we used was 1 m, at which scale it might be challenging to avoid the influence of the micro-topography on the analysis [59]. Some studies have shown that the best resolution did not necessarily provide the best information [35].…”
Section: Rationale For Gully Erosion Susceptibility Mappingmentioning
confidence: 99%
See 1 more Smart Citation
“…The spatial resolution of all the factors we used was 1 m, at which scale it might be challenging to avoid the influence of the micro-topography on the analysis [59]. Some studies have shown that the best resolution did not necessarily provide the best information [35].…”
Section: Rationale For Gully Erosion Susceptibility Mappingmentioning
confidence: 99%
“…With the development of fine-resolution images all over the world [59], large-scale modeling of gully maps will be possible and would be an urgent need for research and management. The results of this research offered a time-efficient, interpretable, and relatively accurate method for gully mapping and would be well applied in future large-scale gully modeling.…”
Section: Future Work and Applicationsmentioning
confidence: 99%
“…The development of unmanned aerial vehicle (UAV) photogrammetry and light detection and ranging (LiDAR) remote sensing can guarantee the data accessibility of high-resolution images. Unlike satellite-based sensors, both aforementioned approaches can create high-resolution topographical data and orthophoto images [42] and simultaneously realise field survey and remote sensing [43,44]. Amongst both approaches, UAV photogrammetry is more flexible and entails a lower cost compared with LiDAR [45].…”
Section: Introductionmentioning
confidence: 99%
“…For a long time, people have been committed to improving the methods of describing and expressing landforms to satisfy the requirements of practical applications, such as textual description, pictographic mapping, and contour maps [9]. Nevertheless, the previous methods are mainly for finer visualization of the landforms, and most of the descriptions of the landforms are qualitative [10,11].…”
Section: Introductionmentioning
confidence: 99%